Laser welding of fused silica glass with sapphire using a non- stoichiometric, fresnoitic Ba2TiSi2O8·3 SiO2 thin film as an absorber. (1st July 2017) - de Pablos-Martín, A.; Lorenz, M.; Grundmann, M.; Höche, Th.
Abstract: Laser welding of dissimilar materials is challenging, due to their difference in coefficients of thermal expansion (CTE). In this work, fused silica-to-sapphire joints were achieved by employment of a ns laser focused in the intermediate Si-enriched fresnoitic glass thin film sealant. The microstructure of the bonded interphase was analyzed down to the nanometer scale and related to the laser parameters used. The crystallization of fresnoite in the glass sealant upon laser process leads to an intense blue emission intensity under UV excitation. This crystallization is favored in the interphase with the silica glass substrate, rather than in the border with the sapphire. The formation of SiO2 particles was confirmed, as well. The bond quality was evaluated by scanning acoustic microscopy (SAM). The substrates remain bonded even after heat treatment at 100 °C for 30 min, despite the large CTE difference between both substrates. Highlights: The laser welding of fused silica glass with a sapphire substrate using a ns pulsed laser is described. A SiO2 -enriched fresnoite glass thin film was successfully used as a sealant. The microstructure of the bond interface was examined through SEM and TEM. The bond interface emits blue luminescence under UV excitation. The substrates remain bonded after heat treatment, despite the great difference in CTE.